Intellectual property protection by incubated companies: Using formal and non-formal methods - Roncalio, Luciano Benvenuti; Richartz, Fernando (REGEPE Entrepreneurship and Small Business Journal, 2021)
Objective: To verify and characterize the use of formal and non-formal methods to protect intellectual property by incubated companies that operate in the health sector. Methodology/approach: Bibliographic research, research with primary sources, and comparative study of the interaction of organizations with the environment. The incubated companies’ primary source information was obtained through face-to-face interviews in field research carried out at the Celta incubator, in Florianópolis/SC, Brazil. Main results: There was an intense use of non-formal methods by the companies studied. The literature adequately predicted non-formal methods adopted by companies. It was also identified that regularity in certifications with Anvisa – Brazilian National Health Surveillance Agency, constitutes an important complementary asset for the appropriation of intellectual property (Teece, 1986) for the companies studied. Theoretical/methodological contributions: Identification of the use of non-formal methods by companies and their composition of use with formal methods contributes to the advancement of literature and business practice. Relevance/originality: This study emphasized research on the use of non-formal methods to protect intellectual property by incubated companies, a topic little explored in the literature. Social and practical contribution: the use of non-formal methods is of particular interest to small and medium-sized companies because their implementation is under the company’s control and, also, because they circumvent the time and costs incurred in the formal registration. It is recommended to expand the understanding concerning the role of complementary assets (Teece, 1986) for technology-based companies. JEL CODE: L26, M13, O00, O30, O32, O34 <!-- End Crossmark Snippet -->